The effect of epoxy and non-epoxy coating treatment on the corrosion of low carbon steel in sodium chloride solutions - Dwinanda, R.P. (Elsevier Ltd, 2020)
Coating is one of the common methods of corrosion prevention for any industries. However it has some limitations such as highly dependable on the composition of coating and could lead to localized corrosion due to damage to the coating from mechanical impact. This experiment aim to investigate the effect of coating on low carbon steel in terms of corrosion rate and material strength by immersion test with 3.5wt NaCl solution for two months with various conditions, i.e., no coating, non-epoxy coating, epoxy coating and damaged (scratched) coating. Initial and final thickness of samples were taken to calculate the estimation average corrosion rate for each experiment condition, and compression test method were used to determine the samples strength. It is shown that coating can decrease corrosion rate for about 78-92 and 18 higher average compression strength as compared to those without coating. Â© 2020 Elsevier Ltd. All rights reserved.